(untitled) (Journal of Comparative & International Higher Education, 2022)
In this study, we explored the notions of cultural learning from non-western perspectives by focusing on the experiences of Chinese undergraduate students from the field of Public Health in the United States of America. We used Weick’s (1995) Sensemaking theory to understand how Chinese undergraduate students made sense of their experiences of learning about other cultures in both personal and professional spaces. We applied a qualitative research design and used interviews, a focus group, and reflection papers for data collection. We found that Chinese undergraduate students focused on social behaviors and attitudes. They used comparison as a tool to make sense of new experiences. Their sensemaking process shifted from simple to complex concepts, and guided learning helped them understand complex social issues related to public health in the U.S. They did not consider learning related to public health knowledge, English language, or life skills as cultural learning.